Islamic Republic of Iran : Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
In this paper, the following statistical data are listed: economic indicators, central government operations, balance of payments, monetary survey, GDP by sectoral origin, gross domestic expenditure at current prices, production, exports, and domestic consumption of oil, natural gas production and uses, crude oil deliveries to domestic refineries, domestic prices for major agricultural products and fertilizers, output, cultivated area, and yield of major crops, education indicators, price developments, central government revenues, value of non-oil exports, exchange rate developments, and so on.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet